System Design of Certified Digital Document Sharing Platform Using Blockchain - Priscilla Jofani Oetomo (Media Informatika, 2021)
This paper aims to build the design of a secure and trustworthy platform of digital document sharing system, where students may share their officially obtained educational documents, e.g. Certificates or Academic Transcripts, with potential employers. The system was designed on top of the Ethereum Blockchain, coupled with IPFS as the document storage system. The design has been arranged in such a way as to work as a nationwide solution.